2019
DOI: 10.1007/s00192-019-04156-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of per-operative antibiotics on the urinary tract infection rate following mid-urethral sling surgery for urinary incontinence: a randomized controlled trial

Abstract: Per-operative antibiotics did not have any impact on the frequency of urinary tract infection following mid-urethral sling application due to stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Modifiable risk factors for postoperative infections have been targeted to decrease infection rates in urology, 6 colorectal surgery, 7 obstetrics, 8 general gynecology, 9 and gynecologic oncology 10 . Interventions aimed at reduction of UTI have included perioperative antibiotic prophylaxis, 11–13 urinary catheter management protocols, 14,15 and utilization of specialized silver alloy–coated urinary catheters 16 . At our institution, a randomized controlled trial by Foxman et al 17 demonstrated that the use of cranberry extract tablets during the postoperative period reduced rates of UTI after gynecologic surgery by 50% 17 .…”
mentioning
confidence: 99%
“…Modifiable risk factors for postoperative infections have been targeted to decrease infection rates in urology, 6 colorectal surgery, 7 obstetrics, 8 general gynecology, 9 and gynecologic oncology 10 . Interventions aimed at reduction of UTI have included perioperative antibiotic prophylaxis, 11–13 urinary catheter management protocols, 14,15 and utilization of specialized silver alloy–coated urinary catheters 16 . At our institution, a randomized controlled trial by Foxman et al 17 demonstrated that the use of cranberry extract tablets during the postoperative period reduced rates of UTI after gynecologic surgery by 50% 17 .…”
mentioning
confidence: 99%